Influencing factors and training strategies for boulder and lead athletes' competitive performance: A narrative review - Liu, S.; Li, Y. (Strength and Conditioning Journal, 2024)
With the introduction of sport climbing in the Olympics, there have been increased opportunities for refining and enhancing the sport. Improving competitive performance is a crucial objective of national development strategies. This narrative review aims to analyze the influencing factors and training strategies for the competitive performance of boulder and lead athletes, providing a reference for improving their competitive performance. Conditioning for boulder and lead involves physical, psychological, and technical training. The competitive performance of boulder and lead athletes is primarily influenced by upper-limb strength, endurance, aerobic capacity, climbing efficiency, route previewing, and psychological elements like confidence, anxiety, and focus. To improve physical fitness and competitive performance, athletes should prioritize enhancing upper-limb strength and endurance. Athletes can enhance their climbing skills and progress by engaging in various international standard climbing routes with varying levels and styles of difficulty, thereby expanding their repertoire of techniques. In addition, there should be an increased emphasis on providing psychological counseling to athletes before competition. In future research, the differences between varying training methods for athletes of different levels and genders should be further explored, along with investigating training and recovery strategies.